Exploring Grammar Learning Needs and Challenges: Insights from an Online Discussion Forum - Kifli, Barli; Nasution, Nazlah Syahaf (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research article explores the grammar learning needs and challenges faced by English language learners through an analysis of questions collected from the online discussion forum. The forum, created by a group of researchers at Universitas Negeri Medan, serves as a platform for learners to seek guidance and support in their grammar learning journey. By conducting qualitative content analysis on 19 questions specifically related to grammar, common themes and patterns regarding grammar challenges were identified. The findings highlight areas of difficulty such as Subject-Verb Agreement, Direct and Indirect Speech, Punctuation (Hyphen usage), Relative Clauses, Understanding